INTERNATIONAL EXPERIENCE INNOVATIVE IMPLEMENTATION IN AGRICULTURE - Amirjanova Dinara Amirzhanovna,; Baytulenov Erekul Saikhanova,; Narenova Ayman Nurmagambetovna,; Kaldykozov Meruert Userbaeva,; Sayabayev Kaysar Maksutovich, (Academic Journal of Physical and Chemical Sciences, 2019)
From the experience of foreign countries, an innovative agrarian economy is formed when agroindustrial production is based mainly on the basis of innovative activity, which is impossible without new technologies for the formation of a single financial and information space. At the same time, the introduction of innovations and the increase in the efficiency of agricultural production are creating new challenges: the industry needs more qualified personnel, at the same time there is a release of workers, which can lead to an increase in unemployment and outflow of the population.